Smart Atensi Margolaras Pati Dalam Pelayanan Rehabilitasi Sosial Bagi Penyandang Disabilitas - Mohammad Fasikhul Lisan Ahmad; Hayat; Agus Zainal Abidin (Jurnal Administrasi Publik dan Pemerintahan, 2026)
This study analyzes the implementation of the Smart ATENSI Margolaras Pati application in social rehabilitation services for persons with disabilities in Gresik Regency. The study aims to examine the implementation of Smart ATENSI in accordance with Minister of Social Affairs Regulation Number 7 of 2022, its impact on the fulfillment of the rights of persons with disabilities, and the challenges faced in its implementation. A descriptive qualitative approach was employed using in-depth interviews, observation, and documentation. The findings show that Smart ATENSI has been implemented in line with the stages of social rehabilitation, including data collection, needs assessment, assistance distribution, and monitoring and evaluation. Digitalization through Smart ATENSI has improved the accuracy of beneficiary targeting, service efficiency, and data transparency. The program has also contributed positively to improving the social functioning of persons with disabilities. However, several challenges remain, particularly related to human resource capacity, digital literacy, internet infrastructure, and the workload of social assistants. Overall, Smart ATENSI represents an effective and inclusive digital innovation in social rehabilitation services in Gresik Regency.